Comparison of iron staining and scoring methods on canine bone marrow aspirates. (2nd March 2021) - Pawsat, Grace A.; Fry, Michael M.; Schneider, Liesel; Schaefer, Deanna M. W.
Abstract: Background: Insufficient iron for erythropoiesis can occur in multiple conditions, including absolute iron deficiency, which is often caused by chronic external hemorrhage in dogs. Distinguishing this from other causes of iron‐restricted erythropoiesis allows appropriate intervention. Decreased marrow iron assessed by Prussian blue staining is a method to diagnose absolute iron deficiency, but scoring systems for marrow iron are not validated in dogs. Objectives: Our objectives were to (a) evaluate the technical performance of two bone marrow iron scoring systems used in human medicine and (b) examine the effects of destaining and restaining on iron stores after Wright‐stained marrow slides are destained and restained with a Prussian blue stain. Methods: Two marrow aspirate slides were included from each of 12 ill dogs in which marrow was collected during clinical evaluation. One slide was directly stained with Prussian blue. The other was first stained with Wright stain, then destained and restained with Prussian blue. Three blinded observers scored the presence of iron in each of the 24 randomized slides using the Gale (scale 0‐6) and sideroblast methods (percentage score). Slides were then re‐randomized and rescored. Results: For the Gale method, interobserver agreement was fair, and intraobserver agreement was substantial to perfect. There was less agreement using the sideroblast method, with a significant observer effect. Iron scores were significantly lower in destained slides compared with those stained directly. Conclusions: Interobserver and intraobserver agreements were acceptable for the Gale method, but the sideroblast method should be used cautiously. A destaining procedure before Prussian blue staining could decrease marrow iron scores.